Adaptation of green onion clones (Allium fistulosum L.) in the high tropic of Nariño, Colombia - Yepes-Chamorro, Dionicio Bayardo; Cadena-Guerrero, Maryory Maricela (Revista de Ciencias Agrícolas, 2025)
Green onion plays a crucial role in the peasant economy of the department of Nariño, Colombia. Therefore, a wide range of varieties adapted to the production area is required. This research aimed to evaluate the adaptation of nine green onion clones through an Agronomic Evaluation Test in three producing environments of Nariño: Pasto, Buesaquillo, and Mueses. The experiment followed a randomized complete block design with four replications, assessing yield, pseudostem length, and pseudostem diameter. A combined analysis of variance was performed for environments, clones, and cuttings. The highest yields of pseudostem were obtained in Obonuco and Buesaquillo, with 49.15 and 48.87 t/ha/cutting, respectively, with clones 1 (65.24), 33 (53.18), 38 (52.15), and 30 (47.66) showing outstanding performance across the three environments. Among the three cuttings, the highest yield was found in cutting 3 with 51.70 t/ha. For pseudostem length, the highest averages were found in Mueses with 31.88 cm and in Buesaquillo with 31.00 cm. The outstanding clones, across the three environments, were 38, 1, 33, and 30, with averages between 28.91 and 36.59 cm. Regarding the diameter of pseudostems, the highest averages were found in Obonuco, with 17.26 mm; the clones that stood out in the environments were 1 (18.15), 28 (17.33), 17 (17.02), and 33 (16.66). Clones 38 and 33 showed the highest averages across all variables, making them strong candidates for further commercial validation to diversify green onion varieties in Nariño.